COVID-19: Contextualizing Misinformation Flows in a US Latinx Border Community (Media and Communication During COVID-19). Issue 5 (23rd November 2021) - Soto-Vásquez, Arthur D.; Gonzalez, Ariadne A.; Shi, Wanzhu; Garcia, Nilda; Hernandez, Jessica
Abstract: This study shows how research on misinformation correction on social media must be contextualized by an understanding of race, class, and local culture. Using an inductive analysis of focus group data, we find that correction of misinformation about the COVID-19 pandemic on the US/Mexico border is multilayered between the family and community institutions. It is also structured by information poverty, local Latinx border practices, and cultural constructs such as chisme and a culture of skepticism. Trust in expert correction is mediated by medical paternalism and distrust of city leadership. Local leaders in the Latinx border community are wary of communicating with the general public and hesitant to correct misinformation in online mediums. Nevertheless, correction of misinformation does occur in the intimate networks of family and friends in online group chats, discussions around the television, and interpersonal communication.